Determinants of Tax Avoidance in Mining Firms: Transfer Pricing, Business Strategy, Political Connections, and Leverage - Nedi Yanto; Mirna Dyah Praptitorini (Universitas Tidar, 2026)
This study aims to analyze the influence of transfer pricing, business strategy, political connections, and leverage on tax avoidance in mining companies listed on the Indonesia Stock Exchange for the 2021–2024 period. In the latest industry classification of the Indonesia Stock Exchange, companies previously classified as mining are now classified into the energy and basic materials sectors. A quantitative approach was employed in this study, while purposive sampling was used for sample selection. The analysis method used was multiple regression with SPSS version 27 to test the influence of each variable on tax avoidance practices. The results showed that transfer pricing had a negative and significant effect on tax avoidance, while business strategy had a positive and significant effect. Meanwhile, political connections and leverage did not significantly influence tax avoidance. These findings indicate that corporate strategy plays a more dominant role in influencing tax avoidance practices compared to political factors or corporate funding structure. The implications of this research indicate that companies need to strengthen compliance in transfer pricing practices and control the aggressiveness of business strategies to minimize tax risks, while emphasizing the importance of implementing good corporate governance in maintaining the company's sustainability and reputation.